A Study of the Antecedents of Smartphone Purchase decision - Rai, Bharat (The International Research Journal of Management Science, 2021)
The main objective of this research paper is to identify the factors affecting consumer behaviorthat influence purchasing decisions on Smartphone users in Nepal. The study examines how the brand image, product features, product price, and social factors influence the purchase decision in the buying of the Smartphone in the Nepalese market. The study focuses on how the consumer preferred to select the Smartphone and which factor has the more influencing role for a purchase decision. Primary data has been used in the research. The data was collected through a structured questionnaire using a convenient sampling technique from 202 customers buying smartphones in Kathmandu. Descriptive statistical analysis, correlation, and Structural Equation Modeling have been used to diagnose and to draw valid conclusions. Brand image, product features, product price, and social factors are taken as independent variables to explore the relationship with purchase decision and impact on the purchase decision. The correlation result showed that all independent variables have a significant relationship with purchase decisions. The Path analysis through SEM result showed that there is a significant impact of brand image, product price, and social factors on the consumer purchase decision. But, the product features have a negative significant impact on purchase decision in the buying of Smartphone in the Nepalese market.